2022
DOI: 10.1109/access.2022.3186786
|View full text |Cite
|
Sign up to set email alerts
|

How Perceptions of Information Privacy and Security Impact Consumer Trust in Crypto-Payment: An Empirical Study

Abstract: The ever-increasing acceptance of cryptocurrencies has fueled applications beyond investment purposes. Crypto-payment is one such application that can bring radical changes to financial transactions in many industries, particularly e-commerce and online retail. However, characteristics of the technology such as transaction disintermediation, lack of central authority, and lack of adequate regulations may introduce new privacy and security concerns among the users. This coincides with another trend of rising in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 109 publications
1
15
0
Order By: Relevance
“…Gonçalves et al ’s (2022) study covered the profiles of the cryptocurrency investors with the aim of understanding their motivations and expectations for the future. Mashatan et al (2022) explored the issue of consumer trust in crypto-payments is formed. They found that perceived information privacy risk, perceived anonymity and perceived traceability of transactions are significant determinants of consumer trust in crypto-payment.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Gonçalves et al ’s (2022) study covered the profiles of the cryptocurrency investors with the aim of understanding their motivations and expectations for the future. Mashatan et al (2022) explored the issue of consumer trust in crypto-payments is formed. They found that perceived information privacy risk, perceived anonymity and perceived traceability of transactions are significant determinants of consumer trust in crypto-payment.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Research demonstrates that regulatory support reduces perceived cryptocurrency risk (Dabbous et al, 2022). A lack of safeguards and institutional structures raises risk perceptions, including exposure to breaches and financial losses (Mashatan et al, 2022). Therefore, we anticipate that the lack of structural assurances contributes to security and privacy risk barriers to crypto‐payment.…”
Section: Modelmentioning
confidence: 99%
“…Despite such advantages, the application of cryptocurrencies in e-commerce and retail transactions as a means of payment for consumer purchases (i.e., crypto-payment) remains much slower than other use-cases (Mashatan et al, 2022). Recent data indicates that 85% of online retailers with annual sales above $1 billion offer their customers with direct or indirect crypto-payment options (PYMNTS, 2022), yet encounter limited consumer interest.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations